PASSIVE PROTAGONISTS AS VESSELS OF POETIC MEANING IN THE FICTION OF KAZUO ISHIGURO - Usmonova Gavkhar Tolib qizi (Modern American Journals, 2025)
This article explores the artistic and psychological significance of passive protagonists in the fiction of Kazuo Ishiguro. The study argues that Ishiguro’s seemingly inactive characters—such as Stevens in The Remains of the Day and Ono in An Artist of the Floating World—serve as vessels for moral introspection and poetic meaning. Their passivity is not a sign of weakness but a stylistic and philosophical device reflecting repression, regret, and ethical consciousness. Drawing on theories of narrative psychology and existential aesthetics, the research highlights how Ishiguro’s restrained narrative form turns stillness into emotional resonance. The analysis demonstrates that through limited agency and controlled self-expression, Ishiguro’s characters embody the tension between silence and self-awareness, ultimately revealing the author’s vision of human dignity, memory, and the quiet endurance of the soul.
Keywords: Passivity, introspection, restraint, identity, moral ambiguity, empathy, characterization, symbolism.